Binocular rivalry produced by temporal frequency differences - Alais, David; Parker, Amanda L. (Frontiers in Human Neuroscience, 2012)
Binocular rivalry occurs when each eye views images that are markedly different. Rather than seeing a binocular fusion of the two, each image is seen exclusively in a stochastic alternation of the monocular images. Here we examine whether temporal frequency differences will trigger binocular rivalry by presenting two random dot arrays that are spatially matched but which modulate temporally at two different rates and contained no net translation. We found that a perceptual alternation between the two temporal frequencies did indeed occur, provided the frequencies were sufficiently different, indicating that temporal information can produce binocular rivalry in the absence of spatial conflict. This finding is discussed with regard to the dependence of rivalry on conflict between spatial and temporal channels.